1998
DOI: 10.4141/p97-055
|View full text |Cite
|
Sign up to set email alerts
|

Alternative weed management strategies in conservation tillage systems for white beans (Phaseolus vulgaris L.)

Abstract: . 1998. Alternative weed management strategies in conservation tillage systems for white bean (Phaseolus vulgaris L.). Can. J. Plant Sci. 78: 363-370. White bean producers often perceive that increased herbicide inputs are required with the adoption of conservation tillage. Acceptance of conservation tillage systems for this crop would increase if effective weed management practices were assured. In 1991 and 1992, various weed management strategies were evaluated in white bean (Phaseolus vulgaris L.) grown wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Morse (1993) found fully mulched soil to have more moisture than partially mulched soil. Hooker et al (1998) found a higher incidence of white bean root rot in no tillage, compared to disked and conventional tillage, which they attributed to prolonged wet conditions observed in the no-tillage plots. In 2001, a combination of higher daily temperatures, lack of rainfall (Table 1), and lower rye residues throughout the growing season may have affected the ability of the soil to conserve moisture.…”
Section: Resultsmentioning
confidence: 94%
“…Morse (1993) found fully mulched soil to have more moisture than partially mulched soil. Hooker et al (1998) found a higher incidence of white bean root rot in no tillage, compared to disked and conventional tillage, which they attributed to prolonged wet conditions observed in the no-tillage plots. In 2001, a combination of higher daily temperatures, lack of rainfall (Table 1), and lower rye residues throughout the growing season may have affected the ability of the soil to conserve moisture.…”
Section: Resultsmentioning
confidence: 94%
“…Rotary hoeing is most effective just before or shortly after weeds emerge (Gunsolus 1990;Oriade and Forcella 1999). A 50 to 80% drop in weed density following rotary hoeing has been reported (Buhler et al 1992;Forcella 2000;Hooker et al 1998;Lovely et al 1958). Weed size and hoeing frequency determine implement efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental and economic considerations have led to the widespread adoption of conservation tillage systems in soybean (Glycine max) in Ontario, Canada. A 1996 estimate showed that about 35% of the soybean crop in Ontario was produced under some form of conservation tillage (Hooker et al 1998). Control of existing weeds has been a major barrier to the success of such tillage systems (Nowak 1983; Wilson and Worsham 1988).…”
Section: Introductionmentioning
confidence: 99%